DEEP REFLECTION ON THE WAR IN EASTERN DRC - Stephano Kinta Issaga; Francis Mwinyisimba; Et Bertin Mwenyimali (IJRDO - Journal of Social Science and Humanities Research, 2025)
This article argues that the ongoing conflict in eastern Democratic Republic of Congo (DRC) is fueled by Rwanda’s aggression, which is supported by Western powers and multinational corporations seeking to exploit the DRC’s vast natural resources. The author highlights the disparity in size and resources between the DRC and Rwanda, criticizes the lack of strong international action against Rwanda, and condemns corruption within the DRC government. The article expresses hope for the DRC’s future and its ability to overcome these challenges.